Quantification of intra-amniotic inflammation in late preterm prelabour rupture of membranes - Marie Vajrychova; Jaroslav Stranik; Rudolf Kupcik; Michaela Sadibolova; Rudolf Kukla; Radka Bolehovska; Marian Kacerovsky (Scientific Reports)
Abstract Preterm prelabour rupture of membranes (PPROM) complicated by intra-amniotic inflammation (IAI) represents a substantial proportion of preterm birth cases. Currently, IAI is frequently defined as amniotic fluid IL-6 concentration above 2,600 pg/mL. However, the amniotic fluid IL-6 concentration was never correlated with the global response of other proinflammatory proteins to the ongoing IAI. In this cross-sectional study, protein quantification was performed using mass spectrometry (MS) analysis followed by target quantification of selected proinflammatory proteins. Levels of amniotic fluid proteins determined by MS were put into the correlation with IL-6 concentration determined by electrochemiluminescence immunoassay method (ECLIA). In total, 925 proteins were efficiently quantified and differential expression analysis revealed 378 proteins upregulated towards IL-6 concentration above 10,000 pg/mL. Four proteins (LCN2, MMP8, MPO, and S100A12) were selected to verify the achieved results and IL-6 concentration of 10,000 pg/mL was determined as the cut-off value for global IAI response.